2018
DOI: 10.1212/wnl.0000000000006456
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation, antithrombotic treatment, and cognitive aging

Abstract: ObjectiveTo examine the association of atrial fibrillation (AF) with cognitive decline and dementia in old age, and to explore the cognitive benefit of antithrombotic treatment in patients with AF.MethodsThis population-based cohort study included 2,685 dementia-free participants from the Swedish National Study on Aging and Care in Kungsholmen, who were regularly examined from 2001–2004 to 2010–2013. AF was ascertained from clinical examination, ECG, and patient registry. Global cognitive function was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 42 publications
9
87
1
2
Order By: Relevance
“…results (data not shown). This finding is consistent with recent studies that have found similar, large protective effects of anticoagulants on the onset of dementia [27,28], which could be through maintaining cerebral blood flow and decreasing the risk of vascular damage to the brain. Most evidence supporting this association is based on observational research within patients having atrial fibrillation; further evidence from a variety of data sources and a broader population is warranted.…”
Section: Discussionsupporting
confidence: 93%
“…results (data not shown). This finding is consistent with recent studies that have found similar, large protective effects of anticoagulants on the onset of dementia [27,28], which could be through maintaining cerebral blood flow and decreasing the risk of vascular damage to the brain. Most evidence supporting this association is based on observational research within patients having atrial fibrillation; further evidence from a variety of data sources and a broader population is warranted.…”
Section: Discussionsupporting
confidence: 93%
“…We found that atrial fibrillation was associated with dementia in men, but not in women. In contrast to our study, the Swedish Kungsholmen study found that atrial fibrillation (after stratifying for sex) was associated with dementia in women, but not in men and one register‐based study from Taiwan found similar risk for dementia in men and women with atrial fibrillation . Our finding that prevalence for atrial fibrillation was higher in men than women is in line with other studies from North America and Europe .…”
Section: Discussionsupporting
confidence: 81%
“…We found a somewhat higher risk (HR 2.9; 95% CI: 1.2–6.8) in our stroke‐free sample than the Whitehall II study (HR 1.67; 95% CI: 1.17, 2.38) and the Adult Changes in Thought (ACT) Study (HR 1.40; 95% CI: 1.08, 1.82) , which also excluded participants with incident stroke. Other community or population‐based studies, taking incident stroke into account by censoring participants at the time of a clinical stroke or adjusting for incident stroke , have shown similar results as the Whitehall II and ACT studies (HR 1.23–1.48).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations